Participatory leadership to improve teacher performance motivation in junior high schools - Lenawati; Munira. AR2; Usman, Nasir (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
Teacher motivation is a common problem found in all schools. This must be addressed in order to achieve the best possible educational outcomes. Therefore, the role of the head teacher is key in creating a conducive educational environment. This study aims to analyse the impact of the implementation of participatory leadership by school principals on performance motivation at SMPN 1 Krueng Sabee and SMP Unggul Calang. This study uses a qualitative approach, including in-depth interviews, participatory observation, and documentary analysis, with two school principals, two deputy principals, and eight teachers. The study's results show a positive and significant relationship between participatory leadership and teacher motivation. Teacher participation in decision-making, clear delegation of authority, discipline, two-way communication, and competency development can substantially increase teachers' dedication, sense of belonging, and enthusiasm in their work. It was concluded that the participatory leadership style model is effective in increasing teachers' intrinsic motivation and performance. The practical implications of this study emphasise the importance of school principals adopting a more collaborative approach in school management.